2001
DOI: 10.1046/j.1365-2249.2001.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of structural variations in the carboxyl terminus of Alzheimer's disease-associated βA4[1–42] amyloid using a monoclonal antibody

Abstract: SUMMARYThe accumulation of amyloid plaques and amyloid congophilic angiopathy (ACA) in the brains of affected individuals is one of the main pathological features of Alzheimer's disease. Within these deposits, the bA4 (Aû) polypeptide represents a major component with the C-terminal 39±43 amino acid variants being most abundant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Fab antibody gene fragments from the mouse monoclonal hybridoma cell line 1E8 [17–22] were generated by PCR using primers generated from immunological sequences in Kabat et al. [20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fab antibody gene fragments from the mouse monoclonal hybridoma cell line 1E8 [17–22] were generated by PCR using primers generated from immunological sequences in Kabat et al. [20].…”
Section: Resultsmentioning
confidence: 99%
“…Epitope mapping (Fig. 7) showed that the 1E8–4b recombinant fragment and the 1E8 antibody recognized the following Aβ peptides: Aβ[5–19], Aβ[8–22], Aβ[11–25], Aβ[14–28] and Aβ[17–31], with 1E8 exhibiting much stronger binding than 1E8–4b against theAβ[5–19] peptide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remodeling protein conformation therefore exposes different structural determinants that can be recognized by different antibodies. Such antibodies have been used to discriminate between the inactive and active conformations of a protein [72], to neutralize viruses [73] and to differentiate between the aggregated or monomeric form of proteins [74][75][76]. When proteins are adsorbed on material surfaces, some epitopes are masked, which reduces the binding of the corresponding antibodies [77][78][79].…”
Section: Evidences Of Material-induced Protein Conformational Changesmentioning
confidence: 99%